Caught in the act : theatricality in the nineteenth-century English novel - Litvak, Joseph (University of California Press, 1992)
In Caught in the Act, Joseph Litvak reveals not only the surprising wealth of theatrical themes in the canonical nineteenth-century English novel, but also the complex and over-determined politics of this theatricality. Nineteenth-century fiction is typically understood as enshrining the bourgeois values of privacy, domesticity, subjectivity, and sincerity. But Litvak demonstrates that private experience in the novels of Jane Austen, Charlotte Bronte, George Eliot, and Henry James is in fact a rigorous enactment of a public script that constructs normative gender and class identities. These novels also display extravagant theatrical forms like travesty, transvestism, charade, and carnival. The theatricality enforces social norms at the same time that it provides ways for novelists to resist them. Litvak thus challenges recent interpretations of the nineteenth-century novel as a disciplinary apparatus. His approach encourages a rethinking of the genre and its varied cultural contexts in all their instability and ambivalence. In addition to a new interpretation, this rethinking offers a new, more frankly theatrical approach to interpretation itself. Litvak argues that the theatricality of the nineteenth-century novel anticipates the late twentieth-century strategies of feminist and gay critical performance.